Restless Leg Syndrome and Sleep Quality in Diabetic Patients with and without Neuropathy - Shumaila Parveen; Sumbal Barnabas; Saira Jahan; Ahyab Mehreen (ziauddin University, 2024)
Background: Restless legs syndrome (RLS), is a condition of uneasy feeling with an uncontrollable urge to move legs. This study was conducted to compare the frequencies of restless leg syndrome and sleep quality in diabetic patients with and without neuropathy. Methods: The comparative cross-sectional was conducted from February to June 2021 at Riphah College of Rehabilitation and Allied health sciences in collaboration with Pakistan Railway Hospital, Rawalpindi. A total of 271 participants were taken after informed consent. Pittsburgh Sleep Quality Index and Restless Leg Syndrome-Disability Index scale were used for assessing the quality of sleep and RLS in all participants, respectively. The relationship between the quality of sleep in diabetic patients with and without neuropathy was assessed by one-way ANOVA. Results: Out of 271 diagnosed cases of diabetes mellitus, 65 (23.9%) were males and 206 (76%) were females. A significant relation (p<0.05) between restless leg syndrome in diabetic patients with neuropathy (2.65±1.36) was observed compared to diabetic patients without neuropathy (1.20±1.44) with p< 0.01. A significant relationship was also found between the quality of sleep in diabetic patients with neuropathy (1.87±0.33). Conclusion: Restless leg syndrome is common in diabetic patients (p<0.05) with neuropathy compared to diabetic patients without neuropathy and sleep quality equally deteriorated in diabetic patients regardless of neuropathy. Keywords: Diabetes Mellitus; Neuropathy; Restless Leg Syndrome; Sleep Quality.